2020
DOI: 10.3390/molecules25051177
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Methoxsalen Supplementation on Chronic Alcohol-induced Osteopenia and Steatosis in Rats

Abstract: Osteopenia or osteoporosis occurs frequently in alcoholics and patients with alcoholic fatty liver disease. Methoxsalen (MTS), 8-methoxypsoralen, improved osteoporosis in ovariectomized and diabetic mouse models; however, its effects on alcohol-induced osteopenia and steatosis have not been reported. This study examined the effects of MTS on alcohol-induced bone loss and steatosis. Rats in the alcohol groups were fed a Liber-DeCarli liquid diet containing 36% of its calories as alcohol. MTS was at 0.005% in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…XAT can inhibit the production of the chondrocyte hypertrophy marker Runt related transcription factor 2 (RUNX2) (Cao et al, 2017), matrix metalloproteinase 13, via the P38-mitogen-activated protein kinase (P38-MAPK/HDAC4) pathway, while further studies showed that XAT decreased the activation of P38 mitogen-activated protease, which in turn increased the expression of histone deacetylated protease 4, thereby inhibiting the production of RUNX2. In an ethanol-induced osteoporosis model (Ham, Choi, Lee, & Lee, 2020), they found that 8-MOP increased serum estradiol, osteocalcin levels and bone alkaline phosphatase activity,…”
Section: Bone Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…XAT can inhibit the production of the chondrocyte hypertrophy marker Runt related transcription factor 2 (RUNX2) (Cao et al, 2017), matrix metalloproteinase 13, via the P38-mitogen-activated protein kinase (P38-MAPK/HDAC4) pathway, while further studies showed that XAT decreased the activation of P38 mitogen-activated protease, which in turn increased the expression of histone deacetylated protease 4, thereby inhibiting the production of RUNX2. In an ethanol-induced osteoporosis model (Ham, Choi, Lee, & Lee, 2020), they found that 8-MOP increased serum estradiol, osteocalcin levels and bone alkaline phosphatase activity,…”
Section: Bone Protectionmentioning
confidence: 99%
“…XAT can inhibit the production of the chondrocyte hypertrophy marker Runt related transcription factor 2 (RUNX2) (Cao et al, 2017), matrix metalloproteinase 13, via the P38‐mitogen‐activated protein kinase (P38‐MAPK/HDAC4) pathway, while further studies showed that XAT decreased the activation of P38 mitogen‐activated protease, which in turn increased the expression of histone deacetylated protease 4, thereby inhibiting the production of RUNX2. In an ethanol‐induced osteoporosis model (Ham, Choi, Lee, & Lee, 2020), they found that 8‐MOP increased serum estradiol, osteocalcin levels and bone alkaline phosphatase activity, and down regulated Receptor activator of nuclear factor‐κB ligand (RANKL), also inhibit the activation of PI3K/AKT, JNK/MAPK, and NF‐κB signaling pathways, thereby enhancing osteoblast differentiation and thus protecting bone structure. Nuclear factor of activated T cells c1 (NFATC1) and TRAP expression to reduce the number of osteoclasts in patients' tissues (Ham, Choi, Lee, & Lee, 2019).…”
Section: Pharmacological Effects Of Xanthotoxinmentioning
confidence: 99%
“…It is a major component of the macular pigment in the human retina and is believed to help protect the eyes from oxidative damage and age-related macular degeneration 48 . Methoxsalen is a naturally occurring compound found in certain plants, including citrus fruits like oranges and lemons, as well as in various plants such as figs and parsley 49 . Methoxsalen is primarily used in a medical procedure known as PUVA (psoralen plus ultraviolet A) therapy, and it is also used to treat skin conditions like psoriasis, vitiligo, and eczema 50 .…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Alkohol merupakan salah satu zat teratogen yang dapat menyebabkan gangguanpada kehamilan Konsumsi alkohol mengakibatkan berbagai efek berbahaya terhadap kesehatan, seperti kerusakan hati, gangguan kognitif, dan gangguan perkembangan embrio (Zakaria et al, 2017). Selain itu, penyakit yang berhubungan dengan konsumsi alkohol kronis diantaranya fatty liver disease, hepatitis, fibrosis, dan sirosis hepar, merupakan penyebab utama kematian bagi pecandu alkohol (Ham et al, 2020). Apabila mengonsumsi alkohol selama kehamilan, dapat menyebabkan kelainan otak dan wajah, keterlambatan pertumbuhan dan kognitif, serta komplikasi neurologis dan perilaku.…”
Section: Pendahuluanunclassified
“…Beberapa penelitian menunjukkan bahwa asupan alkohol yang berlebihan dan berat dikaitkan dengan perubahan bentuk tulang dan peningkatan risiko kerapuhan tulang, meskipun pengaruh alkohol pada pengeroposan tulang masih kontrovesial (Ham et al, 2020). Namun penelitian lain menunjukkan bahwa konsumsi alkohol secara kronis dapat mengganggu metabolisme tulang dan menyebabkan osteoporosis dengan cara menghambat sel-sel osteoblas (Rosa et al, 2019).…”
Section: Pendahuluanunclassified